2018
DOI: 10.1371/journal.pone.0201919
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of problem solving ability in novice programmers

Abstract: Problem Solving (PS) skills allow students to handle problems within an educational context. PS is a core competence of Computer Science education and affects programming success. In this vein, this paper aims to investigate PS ability performance in primary school pupils of a computer course, implemented according to the Neo-Piagetian theory of cognitive development. The study included 945 Slovenian pupils, ranging from fourth to sixth grade. The effects of gender, age and consecutive years of attending the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…The studies that explored gender-related differences in CT or coding have produced contrasting findings. A study by Kožuh et al ( 2018 ) reports finding no gender differences in problem solving skills involved in programming for fourth to sixth graders. Similarly, Papavlasopoulou et al ( 2020 ), who used eye-tracking measures to assess the performance during coding workshops of 8- to 17-year-old students new to coding, a larger age range than Kožuh et al ( 2018 )'s study, report finding no statistically significant difference in gaze behaviors or learning gains between boys and girls.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The studies that explored gender-related differences in CT or coding have produced contrasting findings. A study by Kožuh et al ( 2018 ) reports finding no gender differences in problem solving skills involved in programming for fourth to sixth graders. Similarly, Papavlasopoulou et al ( 2020 ), who used eye-tracking measures to assess the performance during coding workshops of 8- to 17-year-old students new to coding, a larger age range than Kožuh et al ( 2018 )'s study, report finding no statistically significant difference in gaze behaviors or learning gains between boys and girls.…”
Section: Introductionmentioning
confidence: 97%
“…A study by Kožuh et al ( 2018 ) reports finding no gender differences in problem solving skills involved in programming for fourth to sixth graders. Similarly, Papavlasopoulou et al ( 2020 ), who used eye-tracking measures to assess the performance during coding workshops of 8- to 17-year-old students new to coding, a larger age range than Kožuh et al ( 2018 )'s study, report finding no statistically significant difference in gaze behaviors or learning gains between boys and girls. However, some qualitative gender-related differences emerged between girls and boys in the strategies used and in the perceptions of the coding activities.…”
Section: Introductionmentioning
confidence: 97%
“…Most science, mathematics, engineering, and technology programs expect from students to acquire programming skills as a part of their curricula. A universal expectation is that the student should learn the process of solving problems in computer science domain through producing correct programs that compile and behave as expected [1]. Lahtinen, Ala-Mutka, & Järvinen [2] perceived in their study that both students and teachers agreed that practical learning situations were the most useful.…”
Section: Introductionmentioning
confidence: 98%
“…Studies that focused on 'Sociocultural-Related Factors' were observed to have dealt with variables such as like skills prior to and after having learnt programming, learning styles and knowledge map construction (Shaw, 2017), different generation and nonimmigrant students, the performance of problem-solving ability, having prior programming experience (Kim, 2018;Veerasamy, D'Souza, Lindén, & Laakso, 2018), students' selfexplanation quality, number of code edits (Liu, Zhi, Hicks, & Barnes, 2017), computational thinking, spatial and reasoning ability where all variables were found to have some effect on either the learning outcomes of learner characteristics except learning styles, and knowledge map construction. Two studies reported no gender difference in terms of academic achievement in computer science, whereas problem-solving ability was associated positively with performance at the concrete operational stage in one study (Kožuh, Krajnc, Hadjileontiadis, & Debevc, 2018), and significantly correlated with students' self-explanation quality, number of code edits, and prior programming experience in another (Liu et al, 2017). Yet, another study reported significant correlations of at least moderate intensity between computational thinking with spatial ability, reasoning ability, and problem-solving ability.…”
mentioning
confidence: 93%